1985
DOI: 10.1200/jco.1985.3.7.969
|View full text |Cite
|
Sign up to set email alerts
|

Combined modality therapy with radiotherapy, chemotherapy, and immunotherapy in limited small-cell carcinoma of the lung: a Phase III cancer and Leukemia Group B Study.

Abstract: Patients with limited-stage small-cell carcinoma of the lung (SCCL) were randomly assigned to a four-drug chemotherapy program consisting of methotrexate, doxorubicin, cyclophosphamide, and CCNU (MACC) or to a regimen consisting of cyclophosphamide, CCNU, and vincristine alternated with Adriamycin (Adria Laboratories, Columbus, Ohio) and vincristine (CCV/AV). All patients received 4,500 cGy, in a split course, to the primary tumor, mediastinum, and supraclavicular lymph node drainage areas and 3,000 cGy to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…15 Excitement about nonspecific agents was tempered, however, by a randomized study of BCG as adjuvant therapy for SCLC demonstrating no impact on overall survival. 16 In addition, a study of preoperative intra-tumoral injection of BCG found no impact on disease-free or overall survival, 17 however, both of these randomized trials were underpowered to detect small differences. The role of BCG in lung cancer immunotherapy is now primarily as an adjuvant immune stimulant with autologous tumor or antigen-specific vaccine strategies.…”
Section: Early Studies Of Immunotherapy For Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…15 Excitement about nonspecific agents was tempered, however, by a randomized study of BCG as adjuvant therapy for SCLC demonstrating no impact on overall survival. 16 In addition, a study of preoperative intra-tumoral injection of BCG found no impact on disease-free or overall survival, 17 however, both of these randomized trials were underpowered to detect small differences. The role of BCG in lung cancer immunotherapy is now primarily as an adjuvant immune stimulant with autologous tumor or antigen-specific vaccine strategies.…”
Section: Early Studies Of Immunotherapy For Lung Cancermentioning
confidence: 99%
“…31 BEC2-BCG, a vaccine that induces anti-ganglioside GD3 antibodies, was tested in SCLC patients after chemotherapy or combined chemotherapy and radiotherapy. 16 In a large randomized international phase III trial, this agent provided no survival benefit. 32 Polysialic acid, a long polymer of negatively charged sialic acid residues that binds to a neural cell adhesion molecule, has been found on the surface of SCLC tumor cells.…”
Section: Antigen-specific Vaccinationmentioning
confidence: 99%
“…Three trials described in this section used control arms based on the CMC protocol. Maurer et al [ 17] compared continuous MACC therapy to alternation of CCV and AV. Thus, methotrexate was omitted in the alternating treatment arm and no new drug was added.…”
Section: Discussionmentioning
confidence: 99%
“…To judge from the trials until now it is clear that the appropriate patients for treatment are those who have minimal residual disease. It is furthermore clear that immunotherapy is not without toxic side effects (88,89) and finally also that the regrettable fact is that improvement of parameters, such as median survival, has not been accompanied by detectable changes in immune parameters. Monitoring of immunotherapy has proved to be very difficult.…”
Section: Miscellaneousmentioning
confidence: 99%